ANALYZING CORRECTIVE FEEDBACK ON WRITING SKILL AS A MOTIVATION TOOL FOR ESL LEARNERS AT INTERMEDIATE LEVEL: A QUALITATIVE STUDY - Amir Hafeez Malik; Muhammad Riaz; Malik Muhammad Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This qualitative study investigates the effectiveness of corrective feedback on writing skills as a motivation tool for English as Second Language (ESL) learners at the intermediate level. The research aims to explore the impact of providing targeted corrective feedback to motivate students to improve their writing abilities by leading them to identify and rectify their errors in written work. The study adopts a qualitative approach, utilizing semi-structured interviews from ESL teachers and student feedback to gather data from intermediate-level ESL learners. The analysis focuses on identifying patterns and themes related to positive corrective feedback, motivation, teachers' and learners' perception, and teaching learning experiences related to corrective feedback. The findings highlight the impact and effectiveness of corrective feedback as a motivational tool, as it fosters learners' engagement, self-reflection and contribution of the learning process. The research contributes to the field of ESL instruction by emphasizing the role of corrective feedback in promoting learners' motivation and enhancing their writing skills. The implications of the study suggest that ESL teachers should incorporate targeted positive corrective feedback strategies in ESL writing instruction to stimulate students' motivation for their writing skills development.